TRADISI FENG SHUI PADA KELENTENG DI PECINAN SEMARANG - Suliyati, Titiek (Sabda: Jurnal Kajian Kebudayaan, 2011)
Chinese temples of kelenteng in Pecinan Semarang area resemble Chinese temples in Fujian and Guangdong provinces in Southern China. As the building to worship of Budha, Tao, and Confucius, kelenteng is built by applying â€œfeng shuiâ€ principles as tradition in arranging space pattern. The application of â€œfeng shuiâ€ in Chinese kelenteng constitutes the choice of location, site plan, the placement of God and Goddess statues and the usage of color in the ornamentation. Since its establishment until now the application of â€œfeng shuiâ€ in Chinese kelenteng seems unchanged. As the asset of Semarang City, kelenteng is expected to remain eternal because kelenteng can show a characteristic identity or an image of Pecinan or China town complex; as well this complex can be tourism destination in Central Java.